Kesalahan Pembentukan Afiksasi dan Reduplikasi pada Postingan Akun Instagram Dewi Persik (Kajian Morfologi) - Tisya Rexa Oktavia; Mita Marisa Nirditaranti; Firnanda Putria Ananta; Kartika Aulia; Taswirul Afkar (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of language on social media at this time, there are often various errors in word forms in morphology that are interesting to analyze. This happens because social media users such as Instagram express themselves freely without being bound by formal language rules. Social media is also a place where language rules are constantly changing, so that word forms often change. For example, the use of affixes or remixes in social media that is not in accordance with the rules, but is still understood by netizens in more informal communication. This study aims to analyze morphological errors such as affixation and reduplication in @dewiperssik9 Instagram views. The method used in this study is a qualitative descriptive method with a documentation observation approach. Data collected through recording and shooting on the Instagram site display @dewiperssik9 related to affixation and reduplication. The data that has been collected will be analyzed to find morphological changes or irregularities. The results of this study show that there are many errors in the use of affixation and reduplication. These errors include improper prefixes and syphilis, as well as differences in reduplication patterns. These findings show how changes in the use of language in the digital age, can help develop the study of linguistics on social media.